Polityka zagraniczna Federacji Rosyjskiej w myśli strategicznej Zbigniewa Brzezińskiego - Michnik, Wojciech (Przegląd Rusycystyczny, 2012)
Wojciech Michnik Wyższa Szkoła Europejska im. ks. J. Tischnera, Kraków, Poland wmichnik@wse.krakow.pl Воcприятие заграничной политики Роccийcкой Федерации в стратегической мысли Збигнева Бжезиньского Резюме Целью статьи является представление взглядов збигнева Бжезинского на международ-ную политику российской Федерации с учетом постоянных черт и перемен его мысли после окончания холодной войны. Бжезински, являясь одним из самых выдающихся знатоков проблем геополитики, американской и российской международной политики, был и все время остается критическим комментатором участия россии в мировой общественности. В то же время оппоненты Бжезинского обвиняли его в ведении антироссийской политики. В статье представляется характеристика понимания Бже-зинским геополитического поведения россии в период президентуры ельцина и пу-тина. автор статьи отвергает взгляд, согласно которому американский комментатор понимался как противник российского народа. PERCEPTION OF RUSSIAN FEDERATION’S FOREIGN POLICY IN ZBIGNIEW BRZEZINSKI’S STRATEGIC THINKING Summary The article aims to analyze views of Zbigniew Brzezinski regarding continuity and change in Russian Federation’s foreign policy after the end of the Cold War. As a world leading expert on geopolitics, American and Russian foreign policies, Brzezinski has been a careful observer and critical commentator of Russia’s evolving role in world affairs. At the same time, Brzezinski has faced a fierce criticism from Russian and non-Russian opponents alike, who have been accusing him of being anti-Russian in his writings and commentaries. This article addresses these two-above mentioned issues and argues that as far as Brzezinski’s views of Russia are concerned, he has been able to grasp an essence of Russia’s geopolitical evolution during both Yeltsin’s and Putin’s era. With regard to the critics’ accusations, it is showed here that they often mistake (or pretend to mistake) sound if sometimes blunt judgment of Russia’s foreign and internal policies — of which Brzezinski is guilty, with alleged resentment towards Russian nation — which is nowhere to be found in Brzezinski’s writings.